Force tracking model and experimental verification on a novel magnetorheological damper with combined compensator for stay cables of bridge. (August 2021) - Xu, Zhao-Dong; Xu, Yan-Wei; Wang, Cheng; Zhao, Yu-Liang; Ji, Bo-Hai; Du, Yan-Liang
Abstract: As one of the most promising semi-active control devices, magnetorheological (MR) damper has received significant attention in the past few decades because it can offer the adaptability of active control devices in the absence of the associated large power sources. In this study, a new single-rod MR damper with combine volume compensator are proposed, and the design method of combined compensator with independent functions of volume compensation and compensation force is proposed. Then the dynamic tests of the single-rod MR damper are carried out to demonstrate its working performance. The identified sigmoid model is adopted as forward model to characterize the performance of the MR damper. And the force tracking method is put forward by performing inverse of the forward model. Finally, the force tracking simulation of the optimal LQR control force for the stay cable is given to show its feasibility.